Forensic Chemistry : Fundamentals - Grossman, Michael (De Gruyter Textbook, 2021)
FORENSIC CHEMISTRY FUNDAMENTALS strives to help scientists & lawyers,& students, understand how their two disciplines come together for forensic science,in the contexts of analytical chemistry & related science more generally, and thecommon law systems of Canada, USA, UK, the Commonwealth.In this book, forensics is considered more generally than as only for criminallaw; workplace health & safety, and other areas are included. And, two issues ofCanadian legal process are argued as essays in the fi nal two chapters.